Toxicity of sodium metabisulphite on Mysidopsis juniae - Aragão, Janisi Sales; de Castro, Caroline Beserra; Lotufo, Letícia Veras Costa (Arquivos de Ciências do Mar, 2008)
In shrimp farming, sodium metabisulphite is used to prevent the melanosis during harvesting phase, as the animals are sacrificed by thermical shock into a solution of water, ice and sodium metabisulphite, which is normally discharged on the receiving water body. The aim of this work was to evaluate sodium metabisulphite toxicity using the acute toxicity test with Mysidopsis juniae . The LC 50 for sodium metabisulphite was 38.2 ± 4.7 mg/L. In addition, the efficiency of recommended neutralization procedures [aeration and/or Ca(OH) 2 addition] in the reduction of sodium metabisulphite toxicity was evaluated. After 24 hours and no aeration, LC 50 on the absence and presence of Ca(OH) 2 was 36.8 ± 5.6 mg/L and 44.4 ± 3.2mg/L, respectively. After aeration for 24 hours, though this toxicity was significantly reduced (LC 50 = 150.7 ± 8.5mg/L). When the treatments were simultaneous, aeration on the presence of Ca(OH) 2 , toxicity was not observed in three out of five experiments. In attempt to evaluate the toxicity of sodium metabisulphite solution used on the harvesting phase of a marine shrimp farm, the solution was collected directly on the harvesting tank. The LC 50 was lower than 6.25%. Thus, M. juniae showed to be very sensitive to this compound and the chemical treatment by the addition of Ca(OH) 2 in the presence of aeration was efficient in removing its toxicity.